Neurotrophins in the Brain: Interaction With Alcohol Exposure During Development - Boschen, K.E. (Vitam Horm, 2016)
Fetal alcohol spectrum disorders (FASDs) are a result of the teratogenic effects of alcohol on the developing fetus. Decades of research examining both individuals with FASDs and animal models of developmental alcohol exposure have revealed the devastating effects of alcohol on brain structure, function, behavior, and cognition. Neurotrophic factors have an important role in guiding normal brain development and cellular plasticity in the adult brain. This chapter reviews the current literature showing that alcohol exposure during the developmental period impacts neurotrophin production and proposes avenues through which alcohol exposure and neurotrophin action might interact. These areas of overlap include formation of long-term potentiation, oxidative stress processes, neuroinflammation, apoptosis and cell loss, hippocampal adult neurogenesis, dendritic morphology and spine density, vasculogenesis and angiogenesis, and behaviors related to spatial memory, anxiety, and depression. Finally, we discuss how neurotrophins have the potential to act in a compensatory manner as neuroprotective molecules that can combat the deleterious effects of in utero alcohol exposure.